Effects of different LED light curing units on the degree of conversion and microhardness of different composites: FT-IR and SEM-EDX analysis - Bilge, Kuebra; Ipek, Irem (Springer, 2024)
The aim of this study was to evaluate the degree of conversion (DC), Vickers microhardness (VHN), main components and surface properties of a microhybrid and two bulk-fill composite resins polymerized with second and third generation light emitting diodes (LED). Sixty cylindrical specimens of Filtek (TM) Bulk-Fill, everX Posterior (bulk technique) and Filtek Z250 (incremental technique) were prepared in plexiglass molds (5 mm in diameter and 4 mm in thickness) and cured with second-generation LED (Woodpecker LED.B) and third-generation LED (Valo) resulting in six groups (n = 10). DC was determined using Fourier transform infrared spectroscopy (FT-IR), and VHN with Vickers microhardness tester. The main components were identified by means of energy-dispersive X-ray spectroscopy (EDX) microanalysis; whereas filler particles and surface properties were analyzed by scanning electron microscopy (SEM). VHN and DC data were analyzed using two-way ANOVA, followed by t-test with Bonferroni correction for pairwise comparison (p < 0.05). When DC and VHN values were evaluated, after polymerization with second and third generation LED, there was a statistical difference in bulk-fill composites, while there was no statistical difference in microhybrid composite. While, the highest DC and VHN values were obtained after polymerization of Filtek Z250 with Valo, the lowest DC and VHN values were obtained with Filtek Bulk-Fill with Woodpecker LED.B. The degree of conversion and microhardness are affected by the structure of the composite resin and LEDs.
Keywords: Composite resin; FT-IR; LED units; Microhardness; SEM-EDX